User Interface (UI) Design as A Visual Comunication Medium for Composting Waste Management Education - Anastacia, Aurellia; Purbasari, Mita; Jenny Basiroen, Vera (Bina Nusantara University, 2022)
As the fourth leading country with the largest population, the demand for needs in Indonesia has increased significantly, especially in primary needs such as food and household materials. With the massive amount of waste and lack of awareness, the waste we produce is thrown away to the landfill, without knowing the effects it might cause. In this situation, there are many people throwing garbage in the wrong place. The awareness amongst youth in Indonesia in regard to excessive waste and composting as a solution to act on it is, still low. In the effort of collecting data, literature studies from different sources are used, this research also conducts in-depth interviews with experts in the field. A creative solution of creating a digital platform in the form of a website that called Feed the Soil is made to help raise the awareness to solve the problem. With an attractive visual and interactive activity, It would be easier for the targeted audience to be able to increase their interest and boost their knowledge. As a result, the awareness is raised, and information can be easily understood and received in a fun and unordinary way. Moreover, further research is still needed to provide more depth to the platform and implementation.